Survei Aktivitas Dan Kebiasaan Masyarakat Serta Tingkat Resikonya Dalam Menghadapi Wabah COVID-19 Di Indonesia - Hidayatullah, Fajar; Setiawan, Fadibah; Megalini, Farida (Penerbit STKIP PGRI Bangkalan, 2020)
COVID-19 allegedly appeared for the first time in the city of wuhan, but in some discussions there were also those who disagree with this opinion because until now the origin of the virus remained unconfirmed. The transfer of the virus from human to human is very rapid in social groups that are actively engaged. Diligent in maintaining hand hygiene washing it with soap or hand sanitizer is a strategy to prevent the spread of the virus through the touch of a hand because it is suspected that the virus can be spread by contact between both hands with other people or objects that have been exposed to viruses or touches on the face. To measure the validity of the instruments used, the calculation of the reproducibility coefficient and scalability was carried out in this study. Whereas the reliability test used the calculation with Kuder-Richardson20 formula. The Kolmogorov-Smirnov normality test is used to test the normality of data as well as descriptive analysis with a quantitative approach to conclude research. From the results of the study concluded that respondents with habits and high-risk activities are still classified as very little where about 1.5% of 133 respondents or more precisely only 2 respondents included in the category of